2015
DOI: 10.1128/jvi.01118-15
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Detection of Prion Shedding in Saliva and Urine by Chronic Wasting Disease-Infected Deer by Real-Time Quaking-Induced Conversion

Abstract: Chronic wasting disease (CWD) is an emergent, rapidly spreading prion disease of cervids. Shedding of infectious prions in saliva and urine is thought to be an important factor in CWD transmission. To help to elucidate this issue, we applied an in vitro amplification assay to determine the onset, duration, and magnitude of prion shedding in longitudinally collected saliva and urine samples from CWD-exposed white-tailed deer. We detected prion shedding as early as 3 months after CWD exposure and sustained shedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 51 publications
2
116
0
Order By: Relevance
“…We have previously reported that the prion concentration in the sample used to seed the RT-QuIC reaction directly correlates with the rate of amyloid formation (26,27). To explore the kinetics of PrP CWD accumulation in lymphoid tissues over the course of early infection, we compared the average amyloid formation rates in 96GG WTD lymphoid tissues from the 1-to 4-MPE collections with those collected from 3 white-tailed deer with terminal disease (20 to 24 months postinfection).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that the prion concentration in the sample used to seed the RT-QuIC reaction directly correlates with the rate of amyloid formation (26,27). To explore the kinetics of PrP CWD accumulation in lymphoid tissues over the course of early infection, we compared the average amyloid formation rates in 96GG WTD lymphoid tissues from the 1-to 4-MPE collections with those collected from 3 white-tailed deer with terminal disease (20 to 24 months postinfection).…”
Section: Resultsmentioning
confidence: 99%
“…RT-QuIC was performed as previously described (26,27). Briefly, RT-QuIC experiments were carried out in black, optical-bottom 96-well plates (Nunc), with each well containing 0.1 mg/ml SHrPrP substrate and RT-QuIC reaction buffer (20 mM NaH 2 PO 4 , 320 mM NaCl, 1.0 mM EDTA, 1 mM thioflavin T).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-QuIC provides a rapid methodology for analysis of tissues and fluids containing minute quantities of prions (85,86) and may have utility in quantitative and correlative investigations of early and carrier states of prion diseases and potentially other protein misfolding disorders (86)(87)(88)(89). There is little to no evidence that RT-QuIC generates, or represents, the presence of prion infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Deer, elk, moose, sheep, and cattle use their olfactory systems for reproductive, feeding, and exploratory purposes and thus frequently expose their NCs to environmental materials. There are a number of environmental sources of infectious prions, including decaying carcasses (34), placenta (35,36), antler velvet (37), blood (38)(39)(40)(41)(42), urine (43)(44)(45)(46), and feces (47)(48)(49)(50), that could be inhaled into the NC and horizontally transmit disease (7,8) in both captive and free-ranging animal populations. It is worth noting that soil-bound prions remain infectious (19,(51)(52)(53) and that the physical size of the intercellular spaces reported here would accommodate the particle size of silt and clay (between 2 and 50 m), allowing infection from inhaled contaminated soil.…”
Section: Discussionmentioning
confidence: 99%